1990
DOI: 10.1002/jbm.820240503
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsiloxane)‐poly(ethylene oxide)‐heparin block copolymers III: Surface and bulk compositional differences

Abstract: Previously observed bioactivity of poly(dimethylsiloxane)-poly(ethylene oxide)-heparin (PDMS-PEO-Hep) triblock copolymers has prompted studies of the surface and bulk character of this copolymer using angular-dependent electron spectroscopy for chemical analysis (ADESCA), static secondary mass spectroscopy (SIMS), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). Because the low-energy PDMS phase dominates surfaces of this copolymer when solvent cast under air or vacuum conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…It is observed that over 95% of NB‐oligo(EO) is decomposed at 450 °C, while it is only ≈5% for PDMS moiety. Based on previous studies, PDMS is typically stable until around 430 °C, while PEO is likely to be completely decomposed at this temperature . Thus, in this study, the oligo(EO) compositions are estimated from the weight percentage at the 450 °C (see the vertical dashed line in Figure ), which corresponds to the onset of PDMS decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that over 95% of NB‐oligo(EO) is decomposed at 450 °C, while it is only ≈5% for PDMS moiety. Based on previous studies, PDMS is typically stable until around 430 °C, while PEO is likely to be completely decomposed at this temperature . Thus, in this study, the oligo(EO) compositions are estimated from the weight percentage at the 450 °C (see the vertical dashed line in Figure ), which corresponds to the onset of PDMS decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…This confirms previous studies that found that the surface of a PS-PEO film is hydrophobic when exposed to air, but upon exposure to water, the surface of turns rapidly hydrophilic. 27,57 This behavior indicates that the PS block is present at the air/film interface, but upon exposure to water the chains of PS block move away from the water/film interface and are replaced by the more hydrophilic chains of the PEO block.…”
Section: Downloaded By Australian National Univ On July 30 2009mentioning
confidence: 99%
“…This question is important from a fundamental scientific point of view, but it is also significant for applications, because copolymers containing PEO are often being used as biocompatible coatings, and the ability of its films to repel proteins depends crucially on the composition of the top surface. 27,28 Few publications have investigated specifically this aspect. 12,[29][30][31] It is well-known that a PEO layer is in contact with the supporting silicon substrate, given its higher polarity respect to PS.…”
Section: Introductionmentioning
confidence: 99%
“…With this technique it is possible to resolve structural components, such as different domains in polymeric materials [10]. The application of XPS can provide detailed information about the topography and composition in the top layer of a few nm of the surface [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%